Associations between Cannabis Use and Sexual Risk Behavior among Women under Community Supervision: A Brief Report. Issue 2 (3rd April 2021) - Slavin, Melissa N.; Hochstatter, Karli; Kraus, Shane W.; Earleywine, Mitch; El-Bassel, Nabila
Abstract: Objectives: Cannabis use and sexual risk behavior have been found to co-occur, but more research on these associations is needed among criminal justice-involved women (i.e., courts, jails, or prisons). Methods: Regression models examined past 90-day cannabis use on unprotected sex, multiple sexual partners, and STIs/HIV among 306 women under NYC community supervision, adjusting for alcohol, other illicit substances, and socio-demographics. Results: Cannabis use, but not alcohol or other illicit substance use, was positively associated with having unprotected sex and multiple sexual partners, but not STIs or HIV. Conclusions: Criminal justice-involved women may benefit from sexual risk reduction interventions incorporating cannabis content.